Physicochemical stability evaluation of liquid extemporaneous preparation based on tretinoin for administration via enteral tuve - Letícia Mastrangelo COELHO; Alan de Almeida VEIGA; Lauro Mera DE SOUZA; Gisele Mendes DE SOUZA; Vitor Henrique COSTA; Juliane CARLOTTO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: The purpose of the study was to evaluate the content and physicochemical stability of a liquid oral formulation obtained from ATRA gelatin capsules in an oil/water vehicle, given the demand for this formulation for intubated patients undergoing treatment for acute promyelocytic leukemia. Methods: Analyzes were performed using High Performance Liquid Chromatography (HPLC) coupled to a UV detector, using a C-18 column. The run was performed with a mobile phase composed of ultrapure water with 0.5% glacial acetic acid (v/v) as solvent A and acetonitrile as solvent B, in an isocratic run (25:75) (A/B) with a flow of 1 mL/min, temperature at 30°C and detection at 355 nm. The sample injection was 10 μL and the run time was 12 min. The oral formulations were prepared from ATRA (Vesanoid, FQM) in mineral oil/ultrapure water (3:7) (v/v) by dissolution process and heating at 40°C, in oral dosers protected from light and kept under refrigeration (2 - 8°C). Analyzes were performed on days 1, 2, 3, 7, 9 and 14. Results: The extemporaneous preparation showed acceptable visual physical stability, with a change in appearance due to the hardening of aqueous phase, corrected by heating the formulation in water bath at 40°C. The ATRA content was considered adequate until D3 according to the Brazilian Pharmacopeia (FB) 6th edition, presenting 103.3%, 94.8% and 95.6%, on days 1, 2 and 3, respectively. The concentration of isotretinoin, a degradation product, varied from 0.16% to 1.44%, between days 1 and 14, respectively. Conclusion: The results suggested that the liquid oral preparation presented satisfactory content and physicochemical stability for up 48 hours after preparation, when stored protected from light and under refrigeration, as recommended by RDC 67/2007.